PELAKSANAAN PEMBELAJARAN LURING POLA SHIFTING DI SMAN 1 BATUSANGKAR - fauzan, edo okta; Nofrion, Nofrion (JURNAL BUANA, 2023)
Abstract This article is examined to find out the implementation of offline learning with shifting patterns at SMAN 1 Batusangkar in terms of student learning activities and student learning outcomes. This article aims to analyze the implementation of the shifting pattern of offline learning applied at SMAN 1 Batusangkar. Data collection techniques by conducting observations, interviews, and documentation studies. For data analysis used in this study, data from interviews and research questionnaires were carried out at SMAN 1 Batusangkar in 2021. The research method used was a mixed method strengthened by 2 methods, namely qualitative and qualitative. Quantitative analysis is explained by the results of research questionnaires and descriptive interviews. The results of the research conducted found the impact on the offline learning system of shifting patterns at SMAN 1 Batusangkar. Where these impacts affect the learning system carried out at SMAN 1 Batusangkar. The positive impact on offline learning is that shifting patterns help students, teachers, and school officials to interact at school. While the negative impact caused by reducing lesson hours and using the lecture system to divide students into local learning makes students bored and teachers find it difficult to teach. Keywords: Learning, Offline Learning and Shifting Patterns.